Occupational contact allergy: The European perspective–Analysis of patch test data from ESSCA between 2011 and 2020. (31st January 2023) - Bauer, Andrea; Pesonen, Maria; Brans, Richard; Caroppo, Francesca; Dickel, Heinrich; Dugonik, Aleksandra; Larese Filon, Francesca; Geier, Johannes; Gimenez‐Arnau, Ana M.; Napolitano, Maddalena; Patruno, Cataldo; Rustemeyer, Thomas; et al.
Abstract: Background: Occupational skin diseases have led the occupational disease statistics in Europe for many years. Especially occupational allergic contact dermatitis is associated with a poor prognosis and low healing rates leading to an enormous burden for the affected individual and for society. Objectives: To present the sensitization frequencies to the most relevant allergens of the European baseline series in patients with occupational contact dermatitis (OCD) and to compare sensitization profiles of different occupations. Methods: The data of 16 022 patients considered having OCD after patch testing within the European Surveillance System on Contact Allergies (ESSCA) network between January 2011 and December 2020 were evaluated. Patients ( n = 46 652) in whom an occupational causation was refuted served as comparison group. Results: The highest percentages of OCD were found among patients working in agriculture, fishery and related workers, metal industry, chemical industry, followed by building and construction industry, health care, food and service industry. Sensitizations to rubber chemicals (thiurams, carbamates, benzothiazoles) and epoxy resins were associated with at least a doubled risk of OCD. After a decline from 2014 onwards, the risks to acquire an occupation‐related sensitization to methyl(chloro)isothiazolinone (MCI/MI) and especially to methylisothiazolinone (MI) seem to increase again. Sensitization rates to formaldehyde were stable, and to methyldibromo glutaronitrile (MDBGN) slightly decreasing over time. Conclusions: Among allergens in the European Baseline Series, occupational relevance is most frequently attributed to rubber accelerators, epoxy resins and preservatives. Abstract : Among allergens in the European Baseline Series, patch tested within the European Surveillance System on Contact Allergies (ESSCA) network from 2011 to 2020 in patients with occupational contact dermatitis, occupational relevance is most frequently attributed to rubber accelerators, epoxy resins and preservatives.